2015
DOI: 10.1002/glia.22819
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 receptor antagonists as anti‐allodynic agents in acute and sub‐chronic trigeminal sensitization: Role of satellite glial cells

Abstract: Trigeminal (TG) pain often lacks a satisfactory pharmacological control. A better understanding of the molecular cross-talk between TG neurons and surrounding satellite glial cells (SGCs) could help identifying innovative targets for the development of more effective analgesics. We have previously demonstrated that neuronal pro-algogenic mediators upregulate G protein-coupled nucleotide P2Y receptors (P2YRs) expressed by TG SGCs in vitro. Here, we have identified the specific P2YR subtypes involved (i.e., the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 46 publications
8
84
0
Order By: Relevance
“…Unlike ATP, responses of neurons or SGCs to 100 μM ADP were not sensitive to A839977 application (Fig. 9e, f) consistent with previous data from in mouse SGCs that ADP operates mainly via metabotropic P2Y receptors [27,40].…”
Section: Nucleotide Ca 2+ Signaling In Trigeminal Cellssupporting
confidence: 90%
See 2 more Smart Citations
“…Unlike ATP, responses of neurons or SGCs to 100 μM ADP were not sensitive to A839977 application (Fig. 9e, f) consistent with previous data from in mouse SGCs that ADP operates mainly via metabotropic P2Y receptors [27,40].…”
Section: Nucleotide Ca 2+ Signaling In Trigeminal Cellssupporting
confidence: 90%
“…Our functional tests providing a rationale for this finding showed that this is because in the rat trigeminal nociceptive system ADP could be an agonist as efficient as ATP. Specifically, ADP generated large Ca 2+ transients not only in neuron but also in glial cells consistent with previous observations obtained in mouse trigeminal cells [27,40,42]. In glial cells, ADP was even more effective likely due to activation of ADP sensitive P2Y receptors [27,34,35].…”
Section: Basal Levels Of Atp Adp Amp and Adenosine In Meninges Andsupporting
confidence: 90%
See 1 more Smart Citation
“…Using a TgCRND8 mouse model of AD, Ajit, et al (2014) demonstrated both that P2Y 2 expression is enhanced in concert with the AD phenotype, and that genetic deletion of P2Y 2 enhances early AD pathology. In addition P2Y 2 receptors expressed on satellite glia participate in the sensitization leading to trigeminal pain (Magni et al, 2015).…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 99%
“…55,56 There is a need to develop drug-like P2Y2R antagonists which would further validate the therapeutic potential of P2Y2R antagonism in many disease states. Abbreviations Used: ADME absorption, distribution, metabolism, and excretion;…”
Section: Drug-like Antagonists Of the P2y14 Receptor (P2y14r)mentioning
confidence: 99%